Cellular Immunity to Predict the Risk of Cytomegalovirus Infection in Kidney Transplantation: A Prospective, Interventional, Multicenter Clinical Trial. (20th February 2020) - Jarque, Marta; Crespo, Elena; Melilli, Edoardo; Gutiérrez, Alex; Moreso, Francesc; Guirado, Lluís; Revuelta, Ignacio; Montero, Nuria; Torras, Joan; Riera, Lluís; Meneghini, Maria; Taco, Omar; et al.
Abstract: Background: Improving cytomegalovirus (CMV) immune-risk stratification in kidney transplantation is highly needed to establish guided preventive strategies. Methods: This prospective, interventional, multicenter clinical trial assessed the value of monitoring pretransplant CMV-specific cell-mediated immunity (CMI) using an interferon-γ release assay to predict CMV infection in kidney transplantation. One hundred sixty donor/recipient CMV-seropositive (D+/R+) patients, stratified by their baseline CMV (immediate-early protein 1)–specific CMI risk, were randomized to receive either preemptive or 3-month antiviral prophylaxis. Also, 15-day posttransplant CMI risk stratification and CMI specific to the 65 kDa phosphoprotein (pp65) CMV antigen were investigated. Immunosuppression consisted of basiliximab, tacrolimus, mycophenolate mofetil, and corticosteroids in 80% of patients, whereas 20% received thymoglobulin induction therapy. Results: Patients at high risk for CMV based on pretransplant CMI developed significantly higher CMV infection rates than those deemed to be at low risk with both preemptive (73.3% vs 44.4%; odds ratio [OR], 3.44 [95% confidence interval CI, 1.30–9.08]) and prophylaxis (33.3% vs 4.1%; OR, 11.75 [95% CI, 2.31–59.71]) approaches. The predictive capacity for CMV-specific CMI was only found in basiliximab-treated patients for both preemptive and prophylaxis therapy. Fifteen-day CMI risk stratification better predicted CMV infection (81.3% vs 9.1%; OR, 43.33 [95% CI, 7.89–237.96]). Conclusions: Pretransplant CMV-specific CMI identifies D+/R+ kidney recipients at high risk of developing CMV infection if not receiving T-cell–depleting antibodies. Monitoring CMV-specific CMI soon after transplantation further defines the CMV infection prediction risk. Monitoring CMV-specific CMI may guide decision making regarding the type of CMV preventive strategy in kidney transplantation. Clinical Trials Registration: NCT02550639. Abstract : A prospective, interventional, multicenter clinical trial showing the value of cytomegalovirus (CMV)–specific cell-mediated immunity among donor/recipient CMV-seropositive kidney transplant recipients, to identify patients with higher immune susceptibility of developing CMV infection according to the 2 main CMV preventive therapies.